Effects of Hot-Water Extract from Vine Tea (Ampelopsis grossedentata) on Acrylamide Formation, Quality and Consumer Acceptability of Bread - Qian Ma; Shengbao Cai; Yijia Jia; Xiyan Sun; Junjie Yi; Jiang Du (Foods, 2020)
Acrylamide is a harmful substance that could be inhibited by natural products. Vine tea is an edible herb belonging to the Vitaceae family and has been approved by Chinese authorities as a new food ingredient in 2013. However, the effects of vine tea extract on acrylamide formation and bread quality are rarely investigated. In this study, the polyphenol composition of hot-water extract from vine tea was characterized by ultrahigh-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-ESI-HRMS/MS), and its effects on acrylamide formation, quality, and consumer acceptability of bread were investigated. Vine tea extract and its main polyphenol, dihydromyricetin, significantly inhibited the acrylamide formation in bread, especially the low dose of vine tea extract (1.25 g/kg), which decreased the acrylamide formation by 58.23%. The color and texture of bread were significantly affected by vine tea extract or dihydromyricetin, whereas the moisture content was not changed remarkably. Triangle and paired preference tests indicated that, although the aroma, appearance, and taste of the bread with vine tea extract significantly differ from those of the control bread, vine tea extract did not significantly affect the consumer acceptability. In conclusion, the addition of vine tea extract could be used to develop a new and healthy bread product with low acrylamide content.